Prednisolone Induced Systemic Toxicity in Case of Steroid Sensitive Nephrotic Syndrome - Sheth, Nishi; Zaveri, Dhruv; Rajput, Hemraj Singh (Journal of Pharmacy Practice and Community Medicine)
Prednisolone is a corticosteroid, it works on immune system to relieve swelling, redness, and inflammation.it is a choice of drug for arthritis, cancer, asthma, allergic condition, bell’s palsy, Nephrotic syndrome and disorders of endocrine system. Prednisolone helps decreasing inflammation by suppression of leukocytes and decrease expression of pro-inflammatory markers. Nephrotic syndrome is a condition in which damage kidney glomeruli which leaks protein into urine from blood. In pediatric population the choice of drug selected is prednisolone which resolves the symptoms and reduces infection. Prednisolone is the drug considered for the frequently relapsing Nephrotic syndrome. It should be given on alternate basis. for patient with infrequent relapses, therapy should be not prolonged. Adverse effects of prednisolone are hypertension, adrenal suppression, osteoporosis, diabetes mellitus, poor growth and cushingoid syndrome. Systemic toxicity due to prednisolone in pediatric patient increases the risk of infection and pre-renal failure. In this case report, it is summarized that despite of everyday prednisolone intake, alternate day therapy is more effective and causes less side effects. Proper monitoring is necessary and timely laboratory findings should be obtained for less adverse events.
Keywords: Prednisolone; Toxicity; Nephrotic syndrome; Adverse drug reaction; Pre-renal failure.